Efficiency of Sawdust as Low-Cost Adsorbent for Dyes Removal - R. Chikri; N. Elhadiri; M. Benchanaa; Y. El maguana (Journal of Chemistry)
In recent years, the removal of dyes from wastewater has attracted considerable attention due to their harmful effects to ecosystem and human health. Adsorption as a facile and effective technique has been widely used to eliminate a large variety of dyes from aqueous solutions. Activated carbon is the most preferred adsorbent to treat wastewater but its use is limited because of high cost. Therefore, several low-cost and natural materials and wastes have been used as precursors for the preparation of alternative adsorbents. Among them, sawdust as an abundant and low-cost by-product has been explored as adsorbent for the removal of dyes from wastewater. This review focuses on the various sawdust used as a precursor for the preparation of activated carbons. Extensive literature information about sawdust, its compositions, activation methods, its efficiency for dyes removal, and environmental conditions effects has been reviewed. The applicability of various adsorption kinetic models and adsorption isotherm models for dye removal by sawdust-derived activated carbons has been also reported. Finally, this paper highlights the use of sawdust as base material for various composites and mixture which can be used as granular activated carbon.